2013
DOI: 10.1007/s10067-013-2366-4
|View full text |Cite
|
Sign up to set email alerts
|

Serum complement C3 correlates with insulin resistance in never treated psoriatic arthritis patients

Abstract: The objective of this cross-sectional study is to investigate the relationship between inflammatory markers (C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), white blood cell (WBC) count, and complement C3) and insulin resistance (estimated with the surrogate measure homeostasis model assessment of insulin resistance (HOMA-IR)) in Psoriatic arthritis (PsA) patients. Sixty-seven patients with PsA and 138 age- and sex-matched controls were recruited from the Rheumatology Outpatient Clinic of the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 38 publications
2
29
0
1
Order By: Relevance
“…Moreover, two large clinical studies confirmed the association between C3 levels and NAFLD [24,25] independently of other metabolic features. Further, these data integrate our previous studies in which complement C3 was identified as the strongest predictor of insulin resistance in RA and PsA patients [26][27][28], despite in this study, we have not found any significant correlation between the presence of NAFLD and increased insulin resistance, thus supporting the hypothesis that complement C3 may reflect different mechanisms of metabolic derangement. In our cohort we found an overall prevalence of NAFLD in RA of 25%.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, two large clinical studies confirmed the association between C3 levels and NAFLD [24,25] independently of other metabolic features. Further, these data integrate our previous studies in which complement C3 was identified as the strongest predictor of insulin resistance in RA and PsA patients [26][27][28], despite in this study, we have not found any significant correlation between the presence of NAFLD and increased insulin resistance, thus supporting the hypothesis that complement C3 may reflect different mechanisms of metabolic derangement. In our cohort we found an overall prevalence of NAFLD in RA of 25%.…”
Section: Discussionsupporting
confidence: 90%
“…Complement system activation [22] has been shown in liver biopsies from patients with NAFLD compared to healthy controls [23]. Moreover, our group previously demonstrated a significant association between complement C3 and insulin resistance (IR) in psoriatic arthritis (PsA) [26,27] and RA patients [28][29][30]. Moreover, our group previously demonstrated a significant association between complement C3 and insulin resistance (IR) in psoriatic arthritis (PsA) [26,27] and RA patients [28][29][30].…”
Section: Introductionmentioning
confidence: 83%
“…In fact, diagnosis and appropriate treatments may be delayed, due to non-specific findings in the early phases of disease, thus new biomarkers may improve the management of this life-threating syndrome [39][40][41][42]. Although a rigorous process of validation is needed, the use of novel biomarkers in these patients may help physicians, thus improving diagnosis with early recognition and prompt therapy as well as predicting response to treatment and outcome, as suggested in other rheumatic diseases [43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…To explain this phenomenon, a synergy between traditional risk factors and inflammatory disease activity has been proposed 2 . In addition, literature evidence shows that CVD risk factors such as high blood pressure 3 , T2DM 4 , insulin resistance 5, 6 and dyslipidaemia 7 are still underdiagnosed and undertreated in RA patients.…”
Section: Introductionmentioning
confidence: 99%